Liberating Voices in Social Work: The Relevance of Ableism and the Affirmative Model for Capturing Disabled Children's Voices and Views - Flynn, Susan (My University, 2025)
Hearing the voices and experiences of disabled children in social work is an ethical imperative, and at times, even legally compelled. Yet, this is problematic for some disabled children when compared with their majority population peers. The intention is to illustrate the potential of two approaches from disability studies referred to as anti-ableism and the affirmative non-tragedy model of disability, toward extending debates on capturing the voice of disabled children in social work. It is against this backdrop that the paper firstly explores potential attitudinal and knowledge constraints impacting on efforts to capture the voices of disabled children in social work practice. Secondly, this prompts the question of how more thoughtful, deliberate and participatory practice can be achieved in social work, toward hearing the voices and views of disabled children. Responses are theoretically informed and involve provoking conversation and debate rather than claiming to accomplish exhaustive or conclusive answers. For the substantive basis of discussion, a composite theoretical frame is presented. To do this, anti-ableism as an approach is first introduced and explained. This is then informed and extended by a second theory-based innovation from disability studies known as the affirmative non-tragedy model. The overall proposition is, that theoretical approaches from disability studies may aid social workers to better address subtle, embedded forms of disability disadvantage, toward better capturing the voices and experiences of disabled children.
PUBLISHED
Available at https://doi.org/10.1080/13575279.2025.2517075
Keywords: child; youth; voice; non-tragedy; disability